SPONTANEOUS PNEUMOTHORAX AS A POST COVID-19 COMPLICATION - Iv. Novakov; E. Taylor (Trakia Journal of Sciences)
Background. Conditions that appear four weeks after infection with SARS-CoV-2 are accepted as “post COVID”. Spontaneous pneumothorax (SP) is one of these late COVID consequences. Our aim is to present a series of cases with this post COVID complication. Case series. We present four patients with post COVID expression of spontaneous pneumothorax. These patients were non-smokers; never ventilated and had no underlying pre-existing lung diseases and they were treated and recovered from COVID-19 pneumonia in an outpatient setting. Tube thoracostomy, under video-assisted control in three of the patients, was performed as a management of pneumothorax. Conclusion. With these case series, we highlight SP as an expression of long-term COVID-19 morbidity. The effectiveness of thoracoscopy in the diagnosis and management of such type of secondary late COVID-19 spontaneous pneumothorax was demonstrated.